Characteristics of Socio-Alive Building: the case of Bahrain city center - Soliman, Ashraf M.; Alkhalefa, Ali M. (Journal of Architecture and Urbanism, 2018)
Socio-Alive Building is Architecture where people enjoy being around to live within its environment and want to come back after leaving. This paper discusses the terminology of Socio-Alive Building and identifies the building characteristics which make a building social and alive. The main aim of this paper is to discuss the concept of alive-socio building as an approach to keep the building alive and have social role through the consideration of characteristics of socio-alive building. The paper begins by introducing the definitions of Socio-Alive Building and then discusses the characteristics of Socio-Alive Building to construct a theoretical background, then reports the outcomes of a survey in Bahrain to find out perceptions of people of Bahrain toward building characteristics, which could produce socio-alive build environments. A people’s survey concluded significance scale factors of building characteristics that achieve the sociality and alive of the building in Bahrain which were used to evaluate Bahrain City Center. The paper offers ten compromised building characteristics that can produce Socio-Alive with certain significance scale of each. The authors argue that these could be considered during design process to produce socio-alive buildings.